Metode Field Trip dalam pembelajaran Sejarah lokal materi Sejarah Kesultanan Palembang Darussalam (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This paper examines the results of the field trip learning method for 7th-grade students of Al Azhar 33 Palembang Islamic Junior High School in the Social Science subject of Kesultanan Palembang Darussalam Local History. This type of research is descriptive research using a qualitative approach; the data collection technique uses several methods, namely observation, interviews, and documentation. The results of this research show that (1) increasing students’ local history knowledge by applying learning methods that can attract students’ interest in learning so that history learning becomes more alive and teachers do not only provide cognitive knowledge in the classroom, (2) the factors that cause the field trip learning method can be used to increase student’s knowledge is a learning method that teachers can use to facilitate students to learn directly at the location or scene not only the theory in the book, so that students get a concrete, practical and exciting learning experience, (3) The field trip learning method invites students to see the reality that exists regarding the Kesultanan Palembang Darussalam e at the Istana Adat Kesultanan Palembang Darussalam. The results showed an increase in students’ knowledge of local history material of the Kesultanan Palembang Darussalam, as seen through informal and unstructured interviews with 7th-grade Al Azhar 33 Palembang Islamic Junior High School students.
Keywords: Field trip; History learning; Kesultanan Palembang; Darussalam; Local history